Crucial Role of Stromal Interaction Molecule-Activated TRPC-ORAI Channels in Vascular Remodeling and Pulmonary Hypertension Induced by Intermittent Hypoxia - Castillo-Galán, Sebastián; Riquelme, Bárbara; Iturriaga, Rodrigo (Frontiers in Physiology, 2022)
Obstructive sleep apnea (OSA), a sleep breathing disorder featured by chronic intermittent hypoxia (CIH), is associate with pulmonary hypertension. Rats exposed to CIH develop lung vascular remodeling and pulmonary hypertension, which paralleled the upregulation of Stim-activated TRPC-ORAI Ca2+ channels (STOC) in the lung, suggesting that STOC participate in the pulmonary vascular alterations. Accordingly, to evaluate the role played by STOC in pulmonary hypertension we studied whether the STOC blocker 2-aminoethoxydiphenyl borate (2-APB) may prevent the vascular remodeling and the pulmonary hypertension induced by CIH in a rat model of OSA. We assessed the effects of 2-APB on right ventricular systolic pressure (RVSP), pulmonary vascular remodeling, α-actin and proliferation marker Ki-67 levels in pulmonary arterial smooth muscle cells (PASMC), mRNA levels of STOC subunits, and systemic and pulmonary oxidative stress (TBARS) in male Sprague-Dawley (200 g) rats exposed to CIH (5% O2, 12 times/h for 8h) for 28 days. At 14 days of CIH, osmotic pumps containing 2-APB (10 mg/kg/day) or its vehicle were implanted and rats were kept for 2 more weeks in CIH. Exposure to CIH for 28 days raised RVSP > 35 mm Hg, increased the medial layer thickness and the levels of α-actin and Ki-67 in PASMC, and increased the gene expression of TRPC1, TRPC4, TRPC6 and ORAI1 subunits. Treatment with 2-APB prevented the raise in RVSP and the increment of the medial layer thickness, as well as the increased levels of α-actin and Ki-67 in PASMC, and the increased gene expression of STOC subunits. In addition, 2-APB did not reduced the lung and systemic oxidative stress, suggesting that the effects of 2-APB on vascular remodeling and pulmonary hypertension are independent on the reduction of the oxidative stress. Thus, our results supported that STIM-activated TRPC-ORAI Ca2+ channels contributes to the lung vascular remodeling and pulmonary hypertension induced by CIH.